KNOWLEDGE, ATTITUDES AND PRACTICES TOWARDS BREAST CANCER SCREENING PROGRAMS AMONG IRANIAN RURAL FEMALE POPULATIONS IN NORTH OF IRAN: Life Sciences-Medicine - HASSAN KHANI IURIGH; MOHAMMADREZA MAJDI; HASSAN HAJTALEBI; AMENEH GHORBANI; HAMIDREZA HAJTALEBI (International Journal of Life Science and Pharma Research, 2022)
Screening and preventive programs are critical components in the reduction of breast cancer morbidity and mortality. The cross-sectional descriptive study was conducted to investigate the state of knowledge, attitudes, and practices of breast cancer screening programs in Iranian rural female populations. A random sample of women aged from 20 to75 years old in Mazandaran state. Selecting a representative sample of the rural female population within 20 different rural Health-Medical Centers in Mazandaran state had the same probability to be sampled. Women agreeing to participate were given a four-page, self–administered questionnaire. From 3,600 participants 3,044 (84.5%) women complete the questioners. Subject mean age was 34.98±9.1 years with a range of 20 to 81 years. Of all subjects, 60% were married, 48.6% were housewives, and 69.2% had a medium-high education. Knowledge about breast cancer prevention was 10.6% acceptable, 69.6% middle, 19.7% lower and 0.1% unacceptable of the study population. The correct answers ranged from 12.9% to about 65.1%. Most participants had fairly positive attitudes about breast cancer screening. 21.1% of the women performed breast self-examination monthly in the past year. Approximately 80.6% did not undergo a specialist visit once in past two years. In the women 40 years and older, results had suggested 94% (n = 850) didn’t mammography in past two years. Due to inadequate knowledge of women, providing appropriate training in various methods of breast cancer screening for women seems essential to improve knowledge and practice.